2020
DOI: 10.1113/jp278929
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular vesicles in skeletal muscle and systematic adaptation to exercise

Abstract: Regular exercise has a central role in human health by reducing the risk of type 2 diabetes, obesity, stroke and cancer. How exercise is able to promote such systemic benefits has remained somewhat of a mystery but has been thought to be in part mediated by the release of myokines, skeletal muscle‐specific cytokines, in response to exercise. Recent studies have revealed skeletal muscle can also release extracellular vesicles (EVs) into circulation following a bout of exercise. EVs are small membrane‐bound vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 135 publications
(249 reference statements)
1
97
0
1
Order By: Relevance
“…Effectively blocking EV release in a cell type-specific fashion in vivo is complicated and presents a variety of technical challenges. 38 In order to search for candidate muscle fiber genes whose expression is potentially affected by satellite cell EVs during hypertrophy in vivo , we turned to our previously published murine model of inducible satellite cell depletion, the Pax7-Diptheria Toxin A (Pax7-DTA) model. 6 , 8 , 10 Specifically, using an unbiased approach, we aimed to identify genes that were similarly expressed between satellite cell replete and deplete muscle at rest, but were lower in the presence of satellite cells following MOV, which could indicate EV-mediated delivery of repressive microRNAs (miRNAs) to target cells by activated satellite cells.…”
Section: Resultsmentioning
confidence: 99%
“…Effectively blocking EV release in a cell type-specific fashion in vivo is complicated and presents a variety of technical challenges. 38 In order to search for candidate muscle fiber genes whose expression is potentially affected by satellite cell EVs during hypertrophy in vivo , we turned to our previously published murine model of inducible satellite cell depletion, the Pax7-Diptheria Toxin A (Pax7-DTA) model. 6 , 8 , 10 Specifically, using an unbiased approach, we aimed to identify genes that were similarly expressed between satellite cell replete and deplete muscle at rest, but were lower in the presence of satellite cells following MOV, which could indicate EV-mediated delivery of repressive microRNAs (miRNAs) to target cells by activated satellite cells.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the analysis of the methylation profile of cfDNA shows that about 32% of cfDNA is derived from granulocytes, 30% from erythrocyte progenitors, 23% from monocytes and lymphocytes, 9% from endothelial cells, and only 6% from other cells including neurons and hepatocytes [ 11 ], while a sub-characterization for exercise released cfDNA has not been conducted yet. We and others found that next to muscle cells, platelets, endothelial cells, and leukocytes, significantly contribute to the pool of EVs released into plasma following physical exercise (reviewed in [ 47 , 62 , 63 , 64 ]). Like for cfDNA, the underlying signaling mechanisms are not fully understood, but an association with shear stress and the activation of coagulative processes are discussed [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of EV populations and other bioactive particles in blood faces EV research with numerous challenges and, thus, confuses the determination of EVs released into the circulation upon physical exercise (ExerVs). The modalities of ExerV-release, the putative role in adaptation signaling as well as prospective therapeutic and diagnostic applications were recently highlighted and comprehensively summarized (e.g., Trovato et al, 2019 ; Fuller et al, 2020 ; Vechetti et al, 2020 ). Here, we supplement this body of literature with a compilation of the most relevant technical limitations regarding ExerV isolation and characterization, focusing on sEVs.…”
Section: Introductionmentioning
confidence: 99%